Predikante opleiding: Roeping, keuring en legitimering - Nel, Marius (Verbum et ecclesia, 2002)
Training of Pastors: Calling, Testing and Ordination The profession of being a pastor is under pressure. The challenge for churches and seminaries is to rediscover what it means to be called, and more specifically to be called for full time ministry in a local church. Such a calling needs to be secularised in order to be recovered. In this process the "job" of the called one needs to be determined, at least to a larger extent, by the congregation or parish. The point in question here is the fact that such "functions" as pastors are being given by God for equipping the body (Eph 4:7-16). When this is a reality, testing for such a call asks for a commitment to what the call, training for the profession and retaining status imply. Such testing leads to new freedom and the discovery of the complex nature of ministry on the one hand, and giftedness for specific ministries on the other. While further research is needed, the intermediate questions are whether there are seminaries that are willing to partner with churches to find an answer to the growing gap between professional training and church-based-training, and whether there are churches with the courage to take recruitment, testing, and ongoing training more serious.